Cryopreservation of Human Embryonic Liver Cells Using DMSO and High Molecular Weight Polymers - Petrenko, Yu. A. (Problems of Cryobiology and Cryomedicine, 2003)
In this study an influence of high molecular polymers (Dextran, PEO-1500, PEO-3500, PEO-8000) in combination with different concentrations of DMSO was investigated. It is shown that the adding of 10% dextran into cryopreservation media increased neither survival nor viability rates of FL cells after cryopreservation with all the concentrations of DMSO used. At the same time adding of 10% PEO with different molecular weight facilitated the increasing of survival of FL cells. We can see that survival rate depends on molecular weight of PEOs and has been increased with enhancement of molecular weight. Optimal concentration of PEO-8000 (6%) with minimal concentration of DMSO (2%) was found. In these concentrations of CPAs survival rate was significantly higher than with 10% DMSO alone as well as in the presence of fetal calf serum (FCS).